Prevalence of adherence to pharmacological treatment in patients with type 2 diabetes mellitus - Vicenzi, Camila; Moehlecke, Milene (Clinical and Biomedical Research, 2019)
Background: Evidence in the literature indicates that patients with type 2 diabetes (T2D) have a very low level of adherence to pharmacological treatment and that despite several interventions to improve it, a number of obstacles to optimal care limit the extent to which such goals can be achieved. Aims: To assess the sociodemographic profile of patients with T2D, describing prevalence of adherence to drug treatment among them. Additionally, this study attempts to identify the main reasons for nonadherence. Methods: This cross-sectional study evaluated patients with T2D for at least 6 months who are regularly followed at an endocrinology outpatient clinic or who have been admitted to a university hospital. Adherence was assessed by a modified Morisky-Green test and the Batalla test. Results: Ninety-six patients were included, mostly women (59%), white (76%), and with mean age of 52 ± 12 years. Only 49% of patients adhered to drug treatment according to the Batalla test, while 24% were classified as high adherence, 41% as moderate adherence and 34% as low adherence to drug treatment according to the modified Morisky-Green test. Considering glycated hemoglobin levels as a reference method, only 37% of patients were within the currently recommended values, with higher adherence among women compared to men (44% vs. 23%, P = 0.044). Conclusion: The prevalence of adherence among patients with T2D was very low. Older age, insulin therapy and male sex were more strongly associated with worse adherence. The main barrier limiting treatment adherence was lack of motivation, especially due to difficulties in adopting a healthy and balanced diet. Keywords: Type 2 diabetes; adherence; chronic disease